Uproszczenie przy imporcie towarów wynikające z art. 33a ustawy o podatku od towarów i usług - Adam Krychowski (Wrocławsko-Lwowskie Zeszyty Prawnicze)
The import of goods gives rise to a tax liability in VAT. According to the general rules, the taxable person is obliged to calculate and show the amount of VAT in the customs declaration. Then, within 10 days from the date of notification by the customs authority of the amount of tax due, they are obliged to pay the amount of the calculated tax amount. The above solutions can be troublesome. For this reason, it is much more beneficial for taxpayers to apply the simplification under Article 33a of the VAT Law. Its essence is to enable taxable persons to settle the tax due on the importation of goods in a tax return for the period in which the tax liability for the importation of those goods was made. The application of this simplification is subject to certain conditions.